Romantic subjectivity and the endeavor to become a female travel writer in Sangkala di Langit Andalusia by Hanum Salsabiela - Risma Nur Rahmawati (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2026)
This study examines how Hanum Salsabiela reveals herself while in Spain, based on her work entitled "Sangkala di Langit Andalusia-SLA" (2022), published by Republika. SLA can be categorized as a travel writing genre because it is based on the author’s real experiences in a foreign land (Spain). The author reports the places she visited from her own perspective. In addition, SLA can be regarded as postcolonial travel writing because it is produced by writers from formerly colonized regions. While colonial travel writing positions the East as the object of study, Hanum’s work presents a subject from the postcolonial world interpreting the West, Europe. This study employed a qualitative research design. The data were collected through textual observation and note-taking techniques and analyzed using the travel writing paradigms proposed by Thompson and Mills. The findings indicate that Hanum Salsabiela can be categorized as a Romantic Subject or Romantic Self in her travel narrative of Spain. The author not only presents what she observes but also interweaves her personal emotions into the narrative. Moreover, SLA demonstrates the author’s significant endeavors as a female travel writer through the incorporation of dakwah, Islam, and the use of Spanish language elements.